Implementation of European system of regional and national accounts ESA 2010 - Mariusz Dybał (Economic and Environmental Studies (E&ES), 2015)
The aim of the research work was to analyze the implementation of a new methodology in the framework of the European System of Regional and National Accounts ESA 2010. In order to achieve the objective author: i) described the need for a methodology for measuring the economy; ii) discussed the process of improving the methodology of describing the national and regional accounts; iii) presented differences between the ESA 2010 and its predecessor - ESA 1995; iv) determined the effect of changes resulting from the implementation of ESA 2010 to gauge economic growth. The research verified positively established research hypotheses: i) the ESA 2010 introduces significant changes to the existing framework of the system of national and regional accounts in the European Union; ii) ESA 2010 contributes to the increase of economic growth reported by EU Member States; iii) GDP growth in Poland due to use of the ESA 2010 will be limited because of modest expenditure on research and development.
Keywords: P35; H30; H55; H60; 330; national and regional accounts; ESA 2010